Developing Multimedia Package of Local Folktales and Its Impact on Functional English of Rural Children - Vasuki, N.; Mangalambai, A.; Deepa, C. Karthik; Shanthi, S. (INDIAN EDUCATIONAL REVIEW, 2020)
Functional language is a language that is needed in different dayto-day situations like greeting, introducing oneself, asking for or giving advice, explaining rules, apologising, or agreeing and disagreeing. Hence, functional English equips students with the necessary knowledge, skills and understanding to use and apply English in everyday life. Gaining these skills ensures that students can get the most out of their future work and education. The multimedia packages are basically a combination of text, video, sound and graphics with animations. This study investigated the importance of functional English required at all levels for error-free writing of English due to correct grammar aspects from the beginning.